The Impact of Private Sector Internship and Training on Urban Youth in Kenya - Honorati, Maddalena (World Bank, Washington, DC, 2015)
This study uses a randomized experiment to evaluate the impacts of the training and internship program piloted in Nairobi, Mombasa and Kisumu counties by the Kenya Private Sector Alliance and the Government of Kenya with support from the World Bank’s Kenya Youth Empowerment Project. The program provided three months of classroom-based technical training coupled with three months of internships in private firms to vulnerable youths between ages 15 and 29 years, with vulnerable being defined as those out of school and/or with no permanent job. The analysis in this paper is based on survey data collected before the program started (July 2012) and 15 months after the program ended (July 2014). The results of the impact evaluation show that the program has been successful in placing youths in paid jobs and has contributed to an increase of 15 percent in current employment among male participants. The evaluation also found that the program has had positive effects on wage earnings, especially those of females and among older males, with wages increasing by about K Sh 5,000 for males and by K Sh 7,500 for females. With a total unit cost of K Sh 97,000 per beneficiary, an estimated K Sh 6,768 monthly wage for males and K Sh 9,623 monthly wage for females, the program’s benefits exceeded the costs for males and females. The program also encouraged youths to participate in either (certified) skills training or an internship program, and helped to increase the probability of participants’ opening a bank account and accumulating savings (for females).